Nanosized Anatase TiO2 with Exposed (001) Facet for High-Capacity Mg2+ Ion Storage in Magnesium Ion Batteries - Li, Rong; Xia, Liuyan; Yue, Jili; Wu, Junhan; Teng, Xuxi; Chen, Jun; Huang, Guangsheng; Wang, Jingfeng; Pan, Fusheng (Nano-Micro Letters, 2025)
Micro-sized anatase TiO2 displays inferior capacity as cathode material for magnesium ion batteries because of the higher diffusion energy barrier of Mg2+ in anatase TiO2 lattice. Herein, we report that nanosized anatase TiO2 exposed (001) facet doubles the capacity compared to the micro-sized sample ascribed to the interfacial Mg2+ ion storage. First-principles calculations reveal that the diffusion energy barrier of Mg2+ on the (001) facet is significantly lower than those in the bulk phase and on (100) facet, and the adsorption energy of Mg2+ on the (001) facet is also considerably lower than that on (100) facet, which guarantees superior interfacial Mg2+ storage of (001) facet. Moreover, anatase TiO2 exposed (001) facet displays a significantly higher capacity of 312.9 mAh g−1 in Mg–Li dual-salt electrolyte compared to 234.3 mAh g−1 in Li salt electrolyte. The adsorption energies of Mg2+ on (001) facet are much lower than the adsorption energies of Li+ on (001) facet, implying that the Mg2+ ion interfacial storage is more favorable. These results highlight that controlling the crystal facet of the nanocrystals effectively enhances the interfacial storage of multivalent ions. This work offers valuable guidance for the rational design of high-capacity storage systems. Highlights: 1 Nanosized anatase TiO2 exposed (001) facet doubles the capacity compared to the micro-sized sample ascribed to the interfacial Mg2+ ion storage. 2 Anatase TiO2 exposed (001) facet displays a significantly higher capacity of 312.9 mAh g−1 in Mg–Li dual-salt electrolyte. 3 The adsorption energies of Mg2+ on (001) facet are much lower than the adsorption energies of Li+ on (001) facet, implying that the Mg2+ ion interfacial storage is more favorable.